Investigating potent cardioprotective compounds as ACE inhibitors in Saraca asoca - Sonal Prasad; Kaiser Younis; Owais Yousuf (Toxicology Reports)
Saraca asoca is a traditional medicinal plant whose all plant parts are exceptionally effective in terms of antimicrobial, anti-inflammatory, antioxidant, anti-carcinogenic, free radical scavenging,anti-arthritic, and hypolipidemic properties. As cardio-vascular problems occur for many reasons, antioxidants with free radical scavenging properties of plants and herbs are highly effective in treating cardio-related disorders. Though Saraca asoca has been preferred as a tonic and medicinal supplement for women's health, because of the huge variety of bioactive compounds, Saraca asoca needs to be explored for its cardio-protective properties. This review aims to summarize the in vivo and in vitro studies done on Saraca asoca along with the exploration of bioactive compounds in various parts of the plant which will display its cardio-protective potential with its rich bioactive compounds as ACE inhibitors. All relevant information on Saraca asoca in treating and preventing cardio-related disorders has been collected from electronic databases including PubMed, Google Scholar, Web of Science, and Science Direct. Various parts of Saraca asoca were studied to assess its pharmacological and cardioprotective properties. The bioactive compounds of Saraca asoca have been assessed to explore its role as anti-hypertensive, antioxidant, ACE inhibitors, and cardio-protective with the help of in-vivo, in-vitro studies and other research studies. This thorough review focuses on the potent natural bioactive compounds in various parts of Saraca asoca exhibiting its potential as a cardioprotective agent while incorporating historical, chemical, and therapeutic views.